Potency of extemporaneous gentamicin eye drops used in maharaj nakorn chiang mai hospital - Anutra Khangtragool (2018)
This study evaluated the potency of extemporaneous gentamicin (13.6 mg/ml) eye drops, stored for 4 weeks. The effects of different storage temperatures on the antimibrobial potency were examined. Gentamicin (13.6 mg/ml) was prepared with aseptic technique and the solutions stored at 2-8°C and 28°C for 28 days. The fortified stock solutions of gentamicin (13.6 mg/ml) were prepared by reconstituting gentamicin (0.3%) eye drops with gentamicin (40 mg/ml) injection. The potency was evaluated by measuring the minimum inhibitory concentration. Throughout the 28-day period, no change was observed in the minimum inhibitory concentration of gentamicin (13.6 mg/ml) stored at 2-8°C and 28°C. Extemporaneously - prepared gentamicin (13.6 mg/ml) eye drops remained stable at 2-8°C and 28°C for 28 days.